Host specificity in fungal endophytic populations of Quercus ilex and Quercus faginea from Central Spain - Collado, J; Platas, G; Pelaez, F (NOVA HEDWIGIA, 2000)
A comparative study of the endophytic fungal assemblages of Quercus ilex subsp. ballota and Quercus faginea subsp. faginea was carried out on 10 trees growing in a Mediterranean forest in Central Spain. Endophytes from bark, twigs and fresh leaves were isolated from both tree species. As observed for other taxonomically related hosts, a certain overlapping between the endophytic mycoflora in both Quercus species was found. The most frequent fungus in both host species was Pyrenochaeta sp., an anamorph of Dothideales. Nevertheless, a certain degree of host specificity in fungal endophytic infection was detected, when the frequencies of the most commonly isolated endophytes were statistically analysed. The tree species affects significantly the distribution of almost all the fungi with isolation frequencies equal or higher than 2%. Moreover, some dominant fungal taxa could be isolated only from a particular host (Q. ilex or Q. faginea). A cluster analysis of the trees computed on the base of the similarity of their whole of fungal populations confirmed that there is an evident influence of the host species on the composition of the fungal assemblages of the trees. However, this effect does not appear to be always the main determinant of the composition of the fungal assemblages analysed.
Keywords: fungal endophytes; Quercus faginea; Quercus ilex